Pengembangan Instrumen Penilaian Sikap Sosial PKN SD di Masa Pandemi dari Rumah Peserta Didik: Development, Instruments of assessment, social attitudes, pandemics - Danindra Anindita; Beatrix Ela Salu; Eunike Steni Felianti (Arden Jaya Publisher, 2021)
The Covid-19 pandemic is changing for people. All activities undergo change and inhibition.In the world of education, learning is done online by staying at home by each student.In forming the social attitude of learners is not easy and instant by going through a long enough process.Attitude formation can be done by anyone together from the family environment, school, and community Writing this article aims to develop social attitude assessment instruments in the learning of PKN elementary students by posting softwere, namely by google form in the activities of students from home learners in the pandemic period with quantitative research methods using Meta-Analysis research methods conducted by reviewing some results. research in similar topics in the form of books, artike journals and research reports.For readers or further research, it can be done the development of data analysis of attitude assessment in the form of software in order to facilitate teachers and can follow the development in this globalization, where the content of social attitudes in pkn development is also very related, teachers are also not easy in assessing the results of social attitudes of their learners.So, the softwere-shaped assessment for example with Google Form is very flexible in this online application that is the pandemic covid-19.